2020
DOI: 10.1080/20016689.2020.1775933
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of patients after ischaemic stroke treated in a provincial hospital in Poland

Abstract: Background: Ischaemic stroke (IS) is a major cause of death and disability and affects the quality of life of patients. Previous studies focused on urban populations. Objective: To evaluate the health-related quality of life (QoL) of patients with history of IS and living in a rural area in Poland. Patients: Rural population of 172 patients discharged from a district hospital in Zakopane, Poland with a diagnosis of IS in the period from 01.01.2005 to 31.10.2006. Intervention: QoL was evaluated using the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
2
4
0
3
Order By: Relevance
“…In other studies in which self-management interventions were performed in stroke, there was a significant increase in QoL mean total scores in the intervention group compared to the control group (Iltus, 2018;Topcu, 2017). A recent study showed that the most important factors affecting QoL were the functional state, depression and anxiety after ischemic stroke (Jarosławski et al, 2020). Also, a present study described an inversely proportional relationship between the severity of the stroke, disability and QoL (Ramos-Lima et al, 2018).…”
Section: Primary Outcomessupporting
confidence: 69%
“…In other studies in which self-management interventions were performed in stroke, there was a significant increase in QoL mean total scores in the intervention group compared to the control group (Iltus, 2018;Topcu, 2017). A recent study showed that the most important factors affecting QoL were the functional state, depression and anxiety after ischemic stroke (Jarosławski et al, 2020). Also, a present study described an inversely proportional relationship between the severity of the stroke, disability and QoL (Ramos-Lima et al, 2018).…”
Section: Primary Outcomessupporting
confidence: 69%
“…Our study's results align with a previous Malaysian study, highlighting comparable outcomes across different domains of HRQoL [10]. A study in Poland [17] also revealed parallels, with a majority of patients facing di culties in multiple HRQoL domains. Speci cally, 57.3% reported mobility issues, 40.3% encountered challenges in regular activities, 63.2% experienced pain or discomfort, 59% reported anxiety or depression symptoms, and 32.2% faced di culties in self-care.…”
Section: Discussionsupporting
confidence: 89%
“…The evaluation methods are presented in Table 2 . For methods applied, three studies ( 40 , 42 , 46 ) did not specify the survey method, while nine studies ( 25 , 28 , 34 , 36 , 44 , 45 , 53 , 54 , 61 ) used more than one method. The survey methods included telephone interviews ( n = 16, 41.0%), face-to-face interviews ( n = 11, 28.2%), questionnaires during the follow-up visit ( n = 10, 25.6%), and postal questionnaires ( n = 4, 10.3%).…”
Section: Resultsmentioning
confidence: 99%